Resistência à fadiga cíclica de dois instrumentos reciprocantes novos e após três usos: um estudo in vitro - Dalforno, Laura Fagundes (2024)
Objective: The aim of this study was to evaluate the cyclic fatigue resistance of nickeltitanium reciprocating instruments WaveOne Gold (Dentsply Sirona, Ballaigues, Switzerland) and W+ (AllPrime, São José, Brazil), both new and used three times. Methodology: Forty instruments from two systems were used (n=20 per system): WaveOne Gold 25/.07 and W+ 25/.07. Twenty instruments (n=10 per system) were employed to prepare 60 extracted mandibular molars. Each instrument was used to prepare three mandibular molars with three canals and was sterilized after each use. The new instruments and the used instruments were subjected to a cyclic fatigue test, and fragment lengths were measured. The Shapiro-Wilk test was used to evaluate normality in the data distribution. Subsequently, the T test was used for comparisons of cyclic fatigue resistance and the Mann-Whitney test for comparisons of fragment lengths after fracture. A significance level of 5% was considered. Results: WaveOne Gold instruments showed a significant reduction in cyclic fatigue after simulated clinical use (p < .05), while new W+ instruments presented largest fragment length compared to used W+ instruments (p < .05). Scanning electron microscopy showed the parallelogram cross-section and similar and typical characteristics of cyclic fatigue fracture. Dispersive x-ray spectroscopy demonstrated an almost equiatomic distribution of nickel and titanium in the alloy of the tested instruments. Conclusion: Simulated clinical use in three mandibular molars decreased cyclic fatigue resistance of WaveOne Gold instruments, but did not affect the cyclic fatigue resistance of W+ instruments. Furthermore, there was no differences in cyclic fatigue resistance in intergroup comparisons between new instruments nor between used instruments of different systems. New W+ instruments showed largest fragment length compared to used instruments.